Splicing Endonuclease Is an Important Player in rRNA and tRNA Maturation in Archaea - Schwarz, Thandi S.; Berkemer, Sarah J.; Bernhart, Stephan H.; Weiß, Matthias; Ferreira-Cerca, Sébastien; Stadler, Peter F.; Marchfelder, Anita (Frontiers in Microbiology, 2020)
In all three domains of life, tRNA genes contain introns that must be removed to yield functional tRNA. In archaea and eukarya, the first step of this process is catalysed by a splicing endonuclease. The consensus structure recognised by the splicing endonuclease is a bulge-helix-bulge (BHB) motif which is also found in rRNA precursors. So far, a systematic analysis to identify all biological substrates of the splicing endonuclease has not been carried out. In this study, we employed CRISPRi to repress expression of the splicing endonuclease in the archaeon Haloferax volcanii to identify all substrates of this enzyme. Expression of the splicing endonuclease was reduced to 1% of its normal level, resulting in a significant extension of lag phase in H. volcanii growth. In the repression strain, 41 genes were down-regulated and 102 were up-regulated. As an additional approach in identifying new substrates of the splicing endonuclease, we isolated and sequenced circular RNAs, which identified excised introns removed from tRNA and rRNA precursors as well as from the 5´ UTR of the gene HVO_1309. In vitro processing assays showed that the BHB sites in the 5´ UTR of HVO_1309 and in a 16S rRNA-like precursor are processed by the recombinant splicing endonuclease. The splicing endonuclease is therefore an important player in RNA maturation in archaea.